(untitled) (Historia, 2021)
The VOC was founded by a group of Dutch merchants and was one of the first and most succesful multinationals. It represented the history of Western expansion and was an agent of the modern world system and globalisation. But its 1602 charter (Octroy) gave the Company also public authority, the right to make war and peace, and to acquire and govern countries and nations. The historiography of the Company, therefore, can not been restricted to travel, commerce and money, but has to give attention too to state formation and the making of a new society. Seventeenth- and eighteenth cities such as Batavia, Colombo, Malacca and Cape Town demonstrated its vitality, and both modern Indonesia and South Africa are part of its legacy. The formation of the VOC world, of course, had to do with maritime expansion, commercial conflicts and wars, monopolies and colonialism. But that's not the whole story. The creation of the VOC State had also much to do with the encounter of cultures and religions, the meeting of East and West, the moulding of new societies. The VOC State stretched from Cape Town to Nagasaki, its subjects and inhabitants came from many parts of Europe, Africa and Asia, and in many parts of it various ethnic and cultural groups lived next to each other in crowded areas or pluriform cities. How did the VOC State accommodate all these groups and cultures and by which policy did it keep peace and order? It is time for a close scrutiny of the policies that guided the formation of the VOC State and gave Nederlandsch India its identity: at the same time Calvinist and multi-cultural.